The World of Manuscripts and Printed Books in XVI–XVIIth c. GDL: Links and Intersections - Циценене, Рима (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English] This article aims to uncover what knowledge about manuscript books of this time period has been acquired so far, whether the traditional manufacturing style of manuscript books was retained or it was brought closer to the one applied to printed books. Books currently stored in the Manuscript department of the WLLAS were selected as the object of this inquiry. Based on updated dating, 112 exemplars from libraries of Suprasl, Zhyrovichy, Markov and other monasteries were selected and studied de visu in the aspect of Book Science. The results obtained are only preliminary due to a limited number of studied samples. Therefore most remaining exemplars are written in Cyrillic for Orthodox and Uniate Churches. After comparing manuscript and printed books, it is evident that transcription process had been taking place in a two-way manner from the middle of the XVI c. up to the XVII c. While printed books were prepared and printed based solely on manuscripts held in libraries of monasteries, printed books were copied by hand in form of codices. If the first prints were deliberately made to resemble manuscript books, at the middle of the XVII century, scribers and illuminators endeavoured to create manuscript books which would look as similar to printed books as possible. Therefore, it may be concluded the manufacturing tradition of manuscript books was retained and new and functional elements of printed structures were successfully adapted for use in manuscripts.